Sustainable adaptation: Social equity and local climate adaptation planning in U.S. cities. (August 2021) - Fiack, Duran; Cumberbatch, Jeremy; Sutherland, Michael; Zerphey, Nadine
Abstract: Civic leaders have increasingly relied upon local climate adaptation plans to identify vulnerabilities, prioritize goals, and implement actions to prepare cities for the present and projected effects of global climate change. The concept of sustainability is central to these efforts, as climate adaptation discussions are often framed within the context of economic resilience, environmental protection, and social vulnerability. For urban centers, the climate change issue presents unique challenges for each of these dimensions; however, its potential impacts on marginalized populations are extensive. This study draws from the 'just sustainabilities' (Agyeman, Bullard, and Evans 2003) framework and applies the concepts of distributive and procedural justice to examine whether, and to what extent, U.S. cities prioritize social equity concerns in adaptation plans. We perform a qualitative analysis of climate adaptation plans prepared by 22 of the 100 largest U.S. cities. We find that social equity concerns are particularly prominent in local-level climate adaptation discussions relative to those concerning environmental quality and economic development. Highlights: Social equity is a prominent theme in local adaptation plans, relative to environmental protection and economic development Social equity is primarily framed within the context of public health risks and impacts Local adaptation plans primarily focus on addressing intragenerational, rather than intergenerational equity